2012
DOI: 10.1002/pssa.201100816
|View full text |Cite
|
Sign up to set email alerts
|

White light emission from amorphous silicon‐oxycarbide materials

Abstract: This paper reports white photoluminescence (PL) from siliconoxycarbide materials. These are oxidized mesoporous carbon silica (MPCS) and thermally treated rice husk. The PL intensities were strong enough to be detected by the naked eye in daylight under ultraviolet light excitation at room temperature. We investigated the structure, composition, and bonding state of fabricated silicon-oxycarbide materials and found the commonality between the oxidized MPCS and the thermally treated rice husk. Both of them (i) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…Thus, the incorporation of carbon should lead to strain in the network which induces an energy gap change with respect to unstrained silica. Strain would lead to the red‐shift yielding white luminescence in comparison to the UV‐blue luminescence of unstrained silica …”
Section: Properties Of Siocmentioning
confidence: 99%
“…Thus, the incorporation of carbon should lead to strain in the network which induces an energy gap change with respect to unstrained silica. Strain would lead to the red‐shift yielding white luminescence in comparison to the UV‐blue luminescence of unstrained silica …”
Section: Properties Of Siocmentioning
confidence: 99%
“…Although the PL of RH-derived materials was observed, the underlying mechanisms, which are critical to optimize and tune the PL and guide the following work, were not clearly revealed in the previous reports. There is no PL in ideal silica structure because of its wide band gap energy (ca. 9 eV) .…”
Section: Introductionmentioning
confidence: 93%
“…Since RHs contain a high silica content (15–28 wt %), the conversion of RHs to valuable silica or other silicon-containing materials has attracted much attention. The resultant products have found widespread application in adsorption, , catalysis, energy storage, etc. Because silica has a good biocompatibility and high physicochemical and biochemical stabilities, the RH-derived silica and related materials have also shown promising applications in biomedical fields. , Recently, it was reported that the silica derived from RHs can exhibit photoluminescence (PL) by properly adjusting the experimental conditions during synthesis. This finding is of particular significance for its potential biomedical applications, as it avoids introducing extra fluorescent dyes or quantum dots into silica, which is complicated, expensive, and not environmentally benign.…”
Section: Introductionmentioning
confidence: 99%